Bacterial Swarming Reduces Proteus mirabilis and Vibrio parahaemolyticus Cell Stiffness and Increases β-Lactam Susceptibility - George K. Auer (American Society for Microbiology, 2019)
ABSTRACT Swarmer cells of the Gram-negative uropathogenic bacteria Proteus mirabilis and Vibrio parahaemolyticus become long (>10 to 100 μm) and multinucleate during their growth and motility on polymer surfaces. We demonstrated that the increasing cell length is accompanied by a large increase in flexibility. Using a microfluidic assay to measure single-cell mechanics, we identified large differences in the swarmer cell stiffness (bending rigidity) of P. mirabilis (5.5 × 10−22 N m2) and V. parahaemolyticus (1.0 × 10−22 N m2) compared to vegetative cells (1.4 × 10−20 N m2 and 2.2 × 10−22 N m2, respectively). The reduction in bending rigidity (∼2-fold to ∼26-fold) was accompanied by a decrease in the average polysaccharide strand length of the peptidoglycan layer of the cell wall from 28 to 30 disaccharides to 19 to 22 disaccharides. Atomic force microscopy revealed a reduction in P. mirabilis peptidoglycan thickness from 1.5 nm (vegetative cells) to 1.0 nm (swarmer cells), and electron cryotomography indicated changes in swarmer cell wall morphology. P. mirabilis and V. parahaemolyticus swarmer cells became increasingly sensitive to osmotic pressure and susceptible to cell wall-modifying antibiotics (compared to vegetative cells)—they were ∼30% more likely to die after 3 h of treatment with MICs of the β-lactams cephalexin and penicillin G. The adaptive cost of “swarming” was offset by the increase in cell susceptibility to physical and chemical changes in their environment, thereby suggesting the development of new chemotherapies for bacteria that leverage swarming for the colonization of hosts and for survival. IMPORTANCE Proteus mirabilis and Vibrio parahaemolyticus are bacteria that infect humans. To adapt to environmental changes, these bacteria alter their cell morphology and move collectively to access new sources of nutrients in a process referred to as “swarming.” We found that changes in the composition and thickness of the peptidoglycan layer of the cell wall make swarmer cells of P. mirabilis and V. parahaemolyticus more flexible (i.e., reduce cell stiffness) and that they become more sensitive to osmotic pressure and cell wall-targeting antibiotics (e.g., β-lactams). These results highlight the importance of assessing the extracellular environment in determining antibiotic doses and the use of β-lactam antibiotics for treating infections caused by swarmer cells of P. mirabilis and V. parahaemolyticus.